Transcriptional profiling identifies IL-33-expressing intestinal stromal cells as a signaling hub poised to interact with enteric neurons - Topczewska, Patrycja M.; Savvopoulou, Anna; Cosovanu, Catalina; Klose, Christoph S. N. (Frontiers in Cell and Developmental Biology, 2024)
have unveiled a complex network of intercellular connections within diverse tissues, shedding light on the unique properties of different cell types. Central to this intricate network is the cytokine IL-33, which has gained significant attention for its critical role in various diseases, from allergy to cancer, triggering type 2 immune responses, among others. Recent research has challenged the prior assumptions attributing IL-33 expression to epithelial cells, highlighting stromal cells as the predominant source in adipose tissue and the lungs. However, in the complex landscape of the intestine, where IL-33 plays a crucial role in mediating immune surveillance and tolerance and is implicated in many gut-related disorders, its primary source, regulation, and main characteristics need more exploration. This study identifies stromal cells as the primary IL-33-expressing cell type in the small intestine. By investigating their transcriptome and intrinsic signaling pathways, we have uncovered a possible role of IL-33+ stromal cells in maintaining the stem cell niche and their potential crosstalk with neurons relevant to the regulation of axonogenesis. Importantly, our experiments have demonstrated that VIP stimulation of a primary intestinal stromal cell culture significantly amplifies IL-33 expression on mRNA and protein level. Therefore, our study represents a significant leap forward in understanding the plethora of interactions IL-33 + intestinal stromal cells maintain in the intestine, paving the way for future investigations into stromal-neuro crosstalk in the gut. These findings hold great promise for developing targeted therapeutic strategies aimed at harnessing the potential of IL-33 across a spectrum of diseases.